25 Years of Law and Practice at the WTO: Did the Appellate Body Dig its Own Grave?. (18th January 2023) - Van Damme, Isabelle
ABSTRACT: After 25 years of the practice of World Trade Organization (WTO) dispute settlement, the system's ability to continue performing that function has been significantly hampered as a result of the lack of a consensus among WTO Members to (re)appoint Appellate Body Members, resulting in the Appellate Body being defunct as of December 2019. This brief contribution reflects on the various narratives of the causes of the current state of WTO dispute settlement and comments on the role of the Appellate Body. It concludes that no sole responsibility for the current deadlock can be attributed to the Appellate Body. Undoubtedly, the Appellate Body could have decided differently on certain questions. However, asking whether or how the Appellate Body dug its own grave fails to acknowledge the role of WTO Members, collectively and individually, in preserving binding, compulsory WTO dispute settlement providing for appellate review.